A Survey on Teachers' Teaching Strategies in Teaching Vocabulary in Secondary Schools - Helena, Susie Siddl (Universiti Malaysia Sarawak, (UNIMAS), 2007)
This study sets to find out the teachers' teaching strategies in teaching vocabulary in secondary schools. The foci of the study are to find out the strategies used by teachers in teaching vocabulary, problems faced by teachers in teaching vocabulary, strategies perceived as effective in teaching vocabulary and the common strategies employed in teaching vocabulary. The respondents are 200 English teachers from 19 secondary schools in Kuching, Serian, Bau, Lundu and Kota Samarahan. The data for the study is obtained through two instruments - questionnaires and group interviews. The findings reveal that giving examples to explain meaning of a word is the most favoured strategy in teaching vocabulary. The findings also indicate that giving examples is perceived as effective in teaching vocabulary. The majority of the teachers also indicate that words that are overlapping in meaning are difficult to teach. Findings from the interviews also show similarity to the findings from the questionnaires where giving example is indicated as the most common teaching strategy used in teaching vocabulary.